A barium zirconate ceramic-based LTCC raw tape material, LTCC substrate and preparation method thereof
By adjusting the composition of the barium zirconate ceramic-based LTCC raw material, including BaZrO3 ceramic, ZnZrO3 ceramic, silicate ceramic and microcrystalline glass powder, the LTCC casting slurry formed can be co-fired with the silver electrode slurry at low temperatures. , solves the problems of high sintering temperature and high resonance frequency temperature coefficient of barium zirconate ceramics, and realizes high performance LTCC substrate preparation.
Patent Information
- Application Number
- CN202310984783.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-07
AI Technical Summary
In the prior art, the sintering density temperature of barium zirconate ceramics is too high and cannot be co-fired with the silver electrode paste at low temperatures. At the same time, its resonance frequency temperature coefficient is high, which affects the stability of the equipment use.
The LTCC casting slurry formed by using barium zirconate ceramic-based LTCC raw material is cast by adjusting the mass ratio of inorganic materials and organic materials, including BaZrO3 ceramics, ZnZrO3 ceramics, silicate ceramics and microcrystalline glass powder. For molding, it can be co-fired with silver electrode paste at a low temperature of 880 to 920°C.
The co-firing of barium zirconate ceramic-based LTCC material with silver electrode paste at low temperature is realized, reducing the sintering density temperature, and the obtained LTCC substrate has a dielectric constant between 10 and 15 and a dielectric loss between 0.0007 and 0.0015. The temperature coefficient between the resonant frequency is between ±10 ppm/℃ and the flexural strength is above 210 MPa.
Smart Images

Figure CN116986899B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of low temperature co-fired ceramic materials and preparation thereof, and specifically relates to a barium zirconate ceramic-based LTCC raw tape material, an LTCC substrate and a preparation method thereof. Background Art
[0002] In the 5G high-frequency communication era, electronic products are developing towards miniaturization and multifunctionality, which puts higher requirements on the integration and packaging of electronic components, and also drives the development of closely related electronic packaging technology. Electronic packaging technology directly affects the high-speed transmission, power consumption, complexity, reliability and cost of electronic devices and integrated circuits, and therefore becomes a key technology in the field of electronics. As a key technology for the integration of passive components, low-temperature co-fired ceramic (LTCC) technology has significant advantages in the development of high-frequency, high-performance and highly integrated electronic components, and plays a vital role in the development of high-frequency communications in my country.
[0003] LTCC materials with medium and low dielectric constants (10-30) can be used to package the three basic components (resistors, capacitors, inductors) and various passive devices (such as filters, transformers, etc.) in a multi-layer wiring substrate, and integrate them with active devices (such as transistors, IC modules, power MOS, etc.) into a complete circuit system.
[0004] The use environment of electronic components is relatively complex, and the ambient temperature changes greatly. Therefore, the bending strength of the required LTCC material is higher, and the resonant frequency temperature coefficient τf is required to be as close to 0 as possible. Such materials have good impact resistance when used in complex environments, which can ensure that the device will not be easily damaged; the stable resonant frequency will not cause the carrier signal to drift with temperature fluctuations, and will not affect the performance of the equipment.
[0005] BaZrO3 ceramics have a perovskite structure, excellent microwave dielectric properties, excellent thermal stability, and a low thermal expansion coefficient of 8.70*10 between 25 and 1080°C. -6 / ℃, the dielectric constant is about 38.4, and the resonant frequency temperature coefficient is positive. However, the sintering densification temperature of BaZrO3 ceramics exceeds 1700℃, while the melting point of silver electrode is about 961℃. Pure BaZrO3 ceramics cannot be co-fired with silver electrode slurry. Therefore, it is necessary to provide a low-temperature co-fired ceramic material based on barium zirconate ceramic with a low sintering temperature and a resonant frequency temperature coefficient of nearly 0, so that it can be sintered with silver electrode slurry at 880-920℃. Summary of the invention
[0006] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a barium zirconate ceramic-based LTCC raw tape material, an LTCC substrate and a preparation method thereof, so as to solve the problem in the prior art that the sintering densification temperature of barium zirconate ceramics is too high and cannot be co-fired with silver electrode slurry at low temperature, and the problem that the resonant frequency temperature coefficient of barium zirconate ceramics in the prior art is high, which affects the stability of equipment use.
[0007] To achieve the above-mentioned purpose and other related purposes, the present invention provides a barium zirconate ceramic-based LTCC raw tape material, wherein the LTCC raw tape material is formed by tape casting of LTCC tape casting slurry;
[0008] Calculated by mass percentage of the LTCC casting slurry, the LTCC casting slurry includes 45-55wt% of inorganic material components and 45-55wt% of organic material components;
[0009] In terms of the mass percentage of the inorganic material, the inorganic material comprises: 30-70wt% of BaZrO3 ceramics, 0-25wt% of ZnZrO3 ceramics; 1-5wt% of silicate ceramics, and 5-40wt% of microcrystalline glass powder;
[0010] The organic material comprises a solvent, a dispersant, a binder and a plasticizer, and the solvent is an alcohol-ketone mixed solvent.
[0011] Preferably, the silicate ceramic is selected from one or more of CaSiO3 ceramic powder, Zn2SiO4 ceramic powder, Mg2SiO4 ceramic powder, and Li2MgSiO4 ceramic powder.
[0012] Preferably, the microcrystalline glass powder is selected from one or both of BaBSiAl microcrystalline glass powder and CBAlSi microcrystalline glass powder.
[0013] Preferably, in terms of the mass percentage of the BaBSiAl glass-ceramics powder, the BaBSiAl glass-ceramics powder comprises: 20-40wt% BaO, 20-40wt% B2O3, 10-20wt% Al2O3 and 20-50wt% SiO2.
[0014] Preferably, the CBAlSi microcrystalline glass powder comprises, in terms of mass percentage, 20-50wt% of CaO, 10-40wt% of B2O3, 10-40wt% of Al2O3 and 25-50wt% of SiO2.
[0015] Preferably, the preparation method of the BaBSiAl microcrystalline glass powder is: weigh barium carbonate, boric acid, aluminum oxide and silicon powder according to the mass percentage of the raw materials, mix them, melt them at 1500-1550°C for 2-4 hours, and then quench them into glass blocks, sand grind them with a sand grinder, dry them, and sieve them with a 40-mesh sieve to obtain BaBSiAl microcrystalline glass powder.
[0016] Preferably, the preparation method of the CBAlSi microcrystalline glass powder is: calcium carbonate, boric acid, aluminum oxide and silicon powder are weighed according to the mass percentage of the raw materials, mixed, melted at 1400-1550°C for 2-4 hours, then quenched into a glass block, sanded and dried by a sand mill, and sieved with a 40-mesh sieve to obtain the CBAlSi microcrystalline glass powder.
[0017] Preferably, the D50 particle size of the BaZrO3 ceramic, the ZnZrO3 ceramic, and the silicate ceramic is 0.7-1.0 μm.
[0018] Preferably, the D50 particle size of the microcrystalline glass powder is 1.0-2.0 μm.
[0019] The present invention provides a method for preparing a barium zirconate ceramic-based LTCC raw tape material, the preparation method comprising the following steps:
[0020] S1, weighing the inorganic material, solvent and dispersant according to the ratio, putting them into a ball mill filled with zirconium oxide and mixing them by ball milling for 2 to 4 hours, then adding a binder and a plasticizer, and mixing them by ball milling for another 2 to 4 hours to obtain a LTCC casting slurry;
[0021] S2, the LTCC casting slurry is subjected to vacuum degassing and then cast to obtain a LTCC raw tape material.
[0022] The present invention provides a LTCC substrate, which comprises the above-mentioned barium zirconate ceramic-based LTCC raw tape material.
[0023] A method for preparing a LTCC substrate, the method comprising the following steps:
[0024] Providing the above-mentioned barium zirconate ceramic-based LTCC raw tape material;
[0025] The LTCC raw tape material is laminated in multiple layers to form a green blank, which is sintered at 880-920° C. for 150-210 minutes to prepare a LTCC substrate.
[0026] Preferably, at a test frequency of 5 GHz, the obtained LTCC substrate has a dielectric constant of 10 to 15, a dielectric loss of 0.0007 to 0.0015, and a resonant frequency temperature coefficient of ±10 ppm / °C.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The LTCC raw tape material in the present invention is formed by tape casting of LTCC tape slurry. The formed LTCC raw tape material has a smooth surface and uniform thickness. The tape-cast LTCC raw tape material is tightly co-fired with the silver electrode slurry, and there are no bubbles or holes around the silver electrode.
[0029] The Zn in the ZnZrO3 ceramic of the present invention 2+ It can effectively reduce the sintering temperature and ensure that the overall dielectric properties do not decrease; the dielectric loss of silicate ceramics is low, and it can be used as a small material to promote the full crystallization of BaZrO3 ceramics and BaBaSiAl microcrystalline glass powder and CBAlSi microcrystalline glass powder during the sintering process, and optimize and supplement the deficiencies of the dielectric properties of BaZrO3 ceramics, thereby further reducing the dielectric loss of the composite material. However, the amount of silicate ceramics added cannot be too much, as too much will greatly reduce the dielectric constant of the composite material; and the glass resonant frequency temperature coefficient of BaBSiAl microcrystalline glass powder and CBAlSi microcrystalline glass powder is negative, and the dielectric constant is between 6 and 9, and they can be composited with BaZrO3 ceramics to form a LTCC raw tape material with a resonant frequency temperature coefficient of nearly zero and a dielectric constant of 10 to 15; the glass transition temperature of microcrystalline glass powder is 700 to 800°C, and the composite of BaZrO3 ceramics and low-melting-point microcrystalline glass powder can effectively reduce the sintering temperature of BaZrO3 ceramics to obtain LTCC materials with excellent dielectric properties.
[0030] The present invention greatly reduces the sintering densification temperature of BaZrO3 ceramics by adjusting the mass ratio of each component, ensuring that the prepared barium zirconate ceramic-based LTCC raw tape material can be co-fired with the silver electrode slurry at a low temperature of 880-920°C; and the dielectric constant (5GH) of the LTCC substrate stacked by the LTCC raw tape is Z ) varies between 10 and 15, dielectric loss (5GH Z ) fluctuates between 0.0007 and 0.0015, the temperature coefficient of resonance frequency is between ±10ppm / ℃, and the bending strength is above 210MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Shown is the XRD pattern of the BaZrO3 ceramic pre-sintered material formed by pre-sintering at 1200°C for 6h in Examples 1 to 12 of the present invention.
[0032] Figure 2 The SEM image (magnified 4000 times) of the cross section of the LTCC substrate prepared by sintering the LTCC green tape material in Example 1 of the present invention at 880°C for 3 hours.
[0033] Figure 3 The cross-section of the co-fired substrate obtained by co-sintering the LTCC raw tape material and the silver electrode paste at 880° C. for 3 h is shown in SEM image (magnified 630 times) in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The following is an explanation of the embodiments of the present invention by specific examples. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Before further describing the specific embodiments of the present invention, it should be understood that the protection scope of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, not to limit the protection scope of the present invention. The test methods for which specific conditions are not specified in the following examples are generally carried out under conventional conditions or under the conditions recommended by the manufacturers.
[0035] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0036] The invention provides a barium zirconate ceramic-based LTCC raw tape material, wherein the LTCC raw tape material is formed by tape casting of LTCC tape casting slurry; the LTCC tape casting slurry comprises 45-55wt% of inorganic material components and 45-55wt% of organic material components in terms of mass percentage of the LTCC tape casting slurry; the inorganic material comprises: 30-70wt% of BaZrO3 ceramics, 0-25wt% of ZnZrO3 ceramics; 1-5wt% of silicate ceramics, and 5-40wt% of microcrystalline glass powder in terms of mass percentage of the inorganic material; the organic material comprises a solvent, a dispersant, a binder and a plasticizer, and the solvent is an alcohol-ketone mixed solvent.
[0037] Specifically, in terms of the mass percentage of the LTCC casting slurry, the inorganic material component in the LTCC casting slurry may include a value in any range of 45wt%, 47wt%, 49wt%, 51wt%, 53wt%, 55wt%, etc., and the organic material component may include a value in any range of 45wt%, 47wt%, 49wt%, 51wt%, 53wt%, 55wt%, etc. In terms of the mass percentage of the inorganic material, the BaZrO3 ceramic in the inorganic material may include a value in any range of 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, etc.; the ZnZrO3 ceramic may include a value in any range of 0, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, etc., and the Zn in the ZnZrO3 ceramic may include a value in any range of 10wt%, 25wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, etc. 2+ It can effectively reduce the sintering temperature while ensuring that the overall dielectric properties do not decrease; silicate ceramics can include values within any range such as 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, etc.; microcrystalline glass powder can include values within any range such as 5wt%, 15wt%, 25wt%, 35wt%, 40wt%, etc.
[0038] Specifically, in terms of the mass percentage of the organic material, the organic material includes 78-86wt% (such as 78wt%, 80wt%, 82wt%, 84wt%, 86wt% and the like) of solvent, 0.5-2wt% (such as 0.5wt%, 1wt%, 1.5wt%, 2wt% and the like) of dispersant, 10-16wt% (such as 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt% and the like) of binder and 2-6wt% (such as 2wt%, 3wt%, 4wt%, 5wt%, 6wt% and the like) of plasticizer; wherein the solvent is an isopropanol-butanone mixed solvent, the dispersant is selected from one or a combination of castor oil and fish oil, the binder is polyvinyl butyral, and the plasticizer is one or a combination of dioctyl phthalate, polyethylene glycol and dibutyl phthalate. The alcohol-ester mixed solvent selected in the tape casting slurry of the present invention has a low boiling point, is easy to volatilize, has good solubility with the binder, and has a better tape casting effect, so that the surface of the finally prepared LTCC raw tape is smooth and the thickness is uniform.
[0039] As an example, the silicate ceramic is selected from one or more of CaSiO3 ceramic powder, Zn2SiO4 ceramic powder, Mg2SiO4 ceramic powder, and Li2MgSiO4 ceramic powder.
[0040] Specifically, the dielectric loss of silicate ceramics is relatively low, less than 5×10 -4Therefore, it can be used as a small material to promote the full crystallization of BaZrO3 ceramics and microcrystalline glass powder during the sintering process, as well as to optimize and supplement the deficiencies in the dielectric properties of BaZrO3 ceramics, and further reduce the dielectric loss of the composite material. However, the amount of silicate ceramics added cannot be too much, otherwise it will greatly reduce the dielectric constant of the overall composite material.
[0041] As an example, the microcrystalline glass powder is selected from one or two of BaBSiAl microcrystalline glass powder and CBAlSi microcrystalline glass powder. Specifically, the BaBSiAl microcrystalline glass powder and the CBAlSi microcrystalline glass powder are pressed into cylindrical blanks respectively, and the test shows that the sintering glass transition temperature of the blank is 700-800°C, which indicates that the melting temperature of the BaBSiAl microcrystalline glass powder and the CBAlSi microcrystalline glass powder is low. Both microcrystalline glass powders are glasses with low melting points. Compounding them with BaZrO3 ceramics can effectively reduce the sintering densification temperature of BaZrO3 ceramics; and the glass resonant frequency temperature coefficient of the BaBSiAl microcrystalline glass powder and the CBAlSi microcrystalline glass powder is negative, and the dielectric constant is between 6 and 9, which can be compounded with BaZrO3 ceramics to form a LTCC material with a resonant frequency temperature coefficient of nearly zero and a dielectric constant of 10-15.
[0042] As an example, in terms of the mass percentage of the BaBSiAl glass-ceramics powder, the BaBSiAl glass-ceramics powder includes: 20-40wt% BaO, 20-40wt% B2O3, 10-20wt% Al2O3 and 20-50wt% SiO2.
[0043] Specifically, measured in percentage by mass of the BaBSiAl glass-ceramics powder, the BaO content in the BaBSiAl glass-ceramics powder may include values within any range such as 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, etc., the B2O3 content may include values within any range such as 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, etc., the Al2O3 content may include values within any range such as 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, etc., and the SiO2 content may include values within any range such as 20wt%, 30wt%, 40wt%, 50wt%, etc.
[0044] As an example, the preparation method of BaBSiAl microcrystalline glass powder is: barium carbonate, boric acid, aluminum oxide and silicon micropowder are weighed according to the mass percentage of the raw materials, mixed, and melted at 1500-1550°C (such as 1500°C, 1510°C, 1520°C, 1530°C, 1540°C, 1550°C, etc.) for 2-4h (such as 2h, 2.5h, 3h, 3.5h, 4h, etc.), and then quenched into a glass block, sanded and dried by a sand mill, and sieved with a 40-mesh sieve to obtain BaBSiAl microcrystalline glass powder.
[0045] Specifically, the components of the BaBSiAl glass-ceramic powder include BaO, B2O3, Al2O3 and SiO2, BaO is introduced by barium carbonate, B2O3 is introduced by boric acid, and SiO2 is introduced by silicon powder.
[0046] As an example, in terms of mass percentage of the CBAlSi microcrystalline glass powder, the CBAlSi microcrystalline glass powder includes: 20-50wt% CaO, 10-40wt% B2O3, 10-40wt% Al2O3 and 25-50wt% SiO2.
[0047] Specifically, measured in percentage by mass of the CBAlSi glass-ceramics powder, the CaO content in the CBAlSi glass-ceramics powder may include values within any range such as 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc., the B2O3 content may include values within any range such as 10wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, etc., the Al2O3 content may include values within any range such as 10wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, etc., and the SiO2 content may include values within any range such as 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc.
[0048] As an example, the preparation method of CBAlSi microcrystalline glass powder is: calcium carbonate, boric acid, aluminum oxide and silicon powder are weighed according to the mass percentage of the raw materials, mixed, melted at 1400-1550°C (such as 1400°C, 1450°C, 1500°C, 1550°C, etc.) for 2-4h (such as 2h, 2.5h, 3h, 3.5h, 4h, etc.), and then quenched into a glass block, sanded and dried by a sand mill, and sieved with a 40-mesh sieve to obtain CBAlSi microcrystalline glass powder.
[0049] Specifically, the components of CBAlSi microcrystalline glass powder include CaO, B2O3, Al2O3 and SiO2, CaO is introduced by calcium carbonate, B2O3 is introduced by boric acid, and SiO2 is introduced by silicon powder.
[0050] As an example, the D50 particle size of BaZrO3 ceramics, ZnZrO3 ceramics, and silicate ceramics are all 0.7 to 1.0 μm.
[0051] Specifically, the D50 particle size of BaZrO3 ceramics, ZnZrO3 ceramics, and silicate ceramics (CaSiO3 ceramic powder, Zn2SiO4 ceramic powder, Mg2SiO4 ceramic powder, and Li2MgSiO4 ceramic powder) may include values within any range, such as 0.7μm, 0.8μm, 0.9μm, and 1.0μm, and may be adjusted according to actual conditions.
[0052] The preparation method of BaZrO3 ceramics, ZnZrO3 ceramics, CaSiO3 ceramic powders, Zn2SiO4 ceramic powders, Mg2SiO4 ceramic powders and Li2MgSiO4 ceramic powders is as follows: preparing ceramic raw materials according to the molar ratio of oxides (wherein BaO is introduced from barium carbonate, CaO is introduced from calcium carbonate, Li2O is introduced from lithium carbonate, and SiO2 is introduced from silicon micropowder), and mixing the mixture evenly, and pre-calcining at 950-1300° C. for 4-8 hours to obtain BaZrO3 ceramic pre-calcined materials, ZnZrO3 ceramic pre-calcined materials, CaSiO3 ceramic pre-calcined materials, Zn2SiO4 ceramic pre-calcined materials, Mg2SiO4 ceramic pre-calcined materials, Li2 MgSiO4 ceramic pre-calcined material; then use a sand mill and water as the ball milling medium to sand grind the BaZrO3 ceramic pre-calcined material, ZnZrO3 ceramic pre-calcined material, CaSiO3 ceramic pre-calcined material, Zn2SiO4 ceramic pre-calcined material, Mg2SiO4 ceramic pre-calcined material, and Li2MgSiO4 ceramic pre-calcined material for 1 to 2 hours, and the particle size D50 is controlled between 0.7 and 1.0 μm, and then dried in an oven at 120 to 150°C, and sieved with a 40-mesh sieve to obtain the required BaZrO3 ceramic, ZnZrO3 ceramic, CaSiO3 ceramic powder, Zn2SiO4 ceramic powder, Mg2SiO4 ceramic powder, and Li2MgSiO4 ceramic powder.
[0053] As an example, the D50 particle size of the microcrystalline glass powder is 1.0 to 2.0 μm.
[0054] Specifically, the D50 particle size of the microcrystalline glass powder may include values within any range such as 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, etc., and may be adjusted according to actual conditions.
[0055] The present invention also provides a method for preparing the above-mentioned barium zirconate ceramic-based LTCC raw tape material, and the preparation method comprises the following steps:
[0056] S1. Inorganic materials, solvents and dispersants are weighed according to the proportions, put into a ball mill filled with zirconium oxide and mix them for 2 to 4 hours, then a binder and a plasticizer are added, and the mixture is mixed for 2 to 4 hours to obtain LTCC casting slurry;
[0057] S2. The LTCC casting slurry is subjected to vacuum degassing and then cast into a film to obtain a LTCC raw tape material.
[0058] Specifically, measured by the mass percentage of LTCC casting slurry, the LTCC casting slurry includes 45-55wt% of inorganic material components and 45-55wt% of organic material components; measured by the mass percentage of inorganic materials, the inorganic materials include: 30-70wt% of BaZrO3 ceramics, 0-25wt% of ZnZrO3 ceramics; 1-5wt% of silicate ceramics, 5-40wt% of microcrystalline glass powder; the organic materials include solvents, dispersants, binders and plasticizers, and the solvent is an alcohol-ketone mixed solvent; the specific parameters of ball milling can be adjusted according to actual conditions, and no excessive restrictions are made here.
[0059] The present invention also provides a LTCC substrate, which comprises the above-mentioned barium zirconate ceramic-based LTCC raw tape material.
[0060] The present invention also provides a method for preparing a LTCC substrate, comprising the following steps:
[0061] Providing the above-mentioned barium zirconate ceramic-based LTCC raw tape material;
[0062] The LTCC raw tape material is laminated in multiple layers to form a green blank, which is sintered at 880-920°C for 150-180min to prepare an LTCC substrate.
[0063] Specifically, the LTCC raw tape material is cut into a certain size, and after laminating multiple layers, it needs to be vacuumed and then isostatically pressed into a green billet. The green billet is placed in a sintering furnace, first heated to 450°C at a heating rate of 1°C / min at room temperature, and kept at 450°C for 3 hours to remove binder. After the debinding is completed, the temperature is increased to 880-920°C (including any values within the range of 880°C, 890°C, 900°C, 910°C, 920°C, etc.) at a heating rate of 5°C / min, and kept for 150-180min (including any values within the range of 150min, 180min, 210min, etc.), and sintering is completed to prepare the LTCC substrate.
[0064] As an example, at a test frequency of 5 GHz, the dielectric constant of the obtained LTCC substrate is 10-15, the dielectric loss is 0.0007-0.0015, and the resonant frequency temperature coefficient is ±10 ppm / °C.
[0065] Among them, the test method of the dielectric constant and dielectric loss of the LTCC substrate is specifically as follows: the LTCC raw tape material is cut into the required size of 100mm×100mm, 10 layers are cross-stacked, vacuumed, and isostatically pressed into a blank, and then the blank is placed in a sintering furnace, first heated to 450℃ at a heating rate of 1℃ / min at room temperature, and kept at 450℃ for 3h to remove the binder. After the debinding is completed, the temperature is increased to 880-920℃ at a heating rate of 5℃ / min, and kept for 180min to complete the sintering to become a LTCC substrate; then the SPDR separation column dielectric resonant cavity is used to test the dielectric constant and dielectric loss of the LTCC substrate at 5GHz, 3 samples are taken for each formula, and the average value is calculated as the final test data.
[0066] The test method of the resonant frequency temperature coefficient is specifically as follows: the LTCC raw tape material is cut into the required size, 30 to 40 layers are cross-stacked, vacuumed, and isostatically pressed into a blank, and then the blank is cut into a cylinder with a diameter of 20 mm and a height of 5 mm, and then the cylindrical blank is put into a sintering furnace, first heated to 450°C at a heating rate of 1°C / min at room temperature, and kept at 450°C for 3 hours to remove binder, and after the binder removal is completed, the temperature is increased to 880 to 920°C at a heating rate of 5°C / min, and kept for 3 hours to obtain a cylindrical LTCC substrate; then the cylindrical LTCC substrate is placed in a resonant cavity, and then the resonant cavity is placed in a high and low temperature test box to test the resonant frequency temperature coefficient of the cylindrical LTCC substrate between 25 and 85°C.
[0067] The bending strength test method is specifically as follows: the LTCC raw tape material is cut into the required size, 30 to 40 layers are cross-stacked, vacuumed, and isostatically pressed into a blank, and then the blank is cut into strips of 5 mm in height × 5 mm in width × 45 mm in length, and then the strips are placed in a sintering furnace, first heated to 450°C at a heating rate of 1°C / min at room temperature, and kept at 450°C for 3 hours to remove binder, and after the binder is removed, the temperature is raised to 880 to 920°C at a heating rate of 5°C / min, and kept for 180 minutes to obtain a long strip of LTCC substrate; then a universal testing machine is used to test the bending strength of the long strip of LTCC substrate with reference to the GB / T 6569-2006 method.
[0068] In order to better understand the barium zirconate ceramic-based LTCC raw tape material, LTCC substrate and preparation method thereof in the present invention, the present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0069] The preparation methods of the BaZrO3 ceramics, the ZnZrO3 ceramics, the CaSiO3 ceramic powders, the Zn2SiO4 ceramic powders, the Mg2SiO4 ceramic powders, and the Li2MgSiO4 ceramic powders used in the following Examples 1 to 12 and Comparative Examples 1 to 4 are as follows:
[0070] First, prepare the pre-sintered materials of each ceramic:
[0071] The raw materials of BaZrO3 ceramics were prepared according to the molar ratio of oxides, and the mixture was mixed evenly, and pre-fired at 1200℃ for 6h to obtain BaZrO3 ceramic pre-fired material; the raw materials of ZnZrO3 ceramics were prepared according to the molar ratio of oxides, and the mixture was mixed evenly, and pre-fired at 1100℃ for 5h to obtain ZnZrO3 ceramic pre-fired material; the raw materials of CaSiO3 ceramics were prepared according to the molar ratio of oxides, and the mixture was mixed evenly, and pre-fired at 1150℃ for 4h to obtain CaSiO3 ceramic pre-fired material; the raw materials of Zn2 The raw materials of SiO4 ceramics are prepared according to the molar ratio of oxides, and the mixture is mixed evenly, and pre-fired at 1200°C for 4 hours to obtain Zn2SiO4 ceramic pre-fired materials; the raw materials of Mg2SiO4 ceramics are prepared according to the molar ratio of oxides, and the mixture is mixed evenly, and pre-fired at 1250°C for 4 hours to obtain Mg2SiO4 ceramic pre-fired materials; the raw materials of Li2MgSiO4 ceramics are prepared according to the molar ratio of oxides, and the mixture is mixed evenly, and pre-fired at 980°C for 6 hours to obtain Li2MgSiO4 ceramic pre-fired materials;
[0072] Then, the pre-sintered BaZrO3 ceramic, ZnZrO3 ceramic, CaSiO3 ceramic, Zn2SiO4 ceramic, Mg2SiO4 ceramic and Li2MgSiO4 ceramic were sand-milled for 1 hour using a sand mill and water as the ball milling medium. The particle size D50 was controlled between 0.7 and 1.0 μm. The pre-sintered BaZrO3 ceramic, ZnZrO3 ceramic, CaSiO3 ceramic powder, Zn2SiO4 ceramic powder, Mg2SiO4 ceramic powder and Li2MgSiO4 ceramic powder were then dried in an oven at 120°C and sieved through a 40-mesh sieve to obtain BaZrO3 ceramic, ZnZrO3 ceramic, CaSiO3 ceramic powder, Zn2SiO4 ceramic powder, Mg2SiO4 ceramic powder and Li2MgSiO4 ceramic powder with a particle size of 0.7 to 1.0 μm.
[0073] See also Figure 1 This is the XRD diagram of the BaZrO3 ceramic pre-fired material formed by pre-firing at 1200℃ for 6h. It can be seen from the figure that pure BaZrO3 ceramic crystal phase can be formed at a temperature of 1200℃, and no other impure crystal phases can be seen.
[0074] The component proportions of the BaBSiAl glass-ceramic powder and the CBAlSi glass-ceramic powder used in the following Examples 1 to 12 and Comparative Examples 1 to 4 are shown in Table 1 and Table 2, respectively. The preparation method of the BaBSiAl glass-ceramic powder is as follows: weigh barium carbonate, boric acid, aluminum oxide and silicon powder according to the mass percentage of the raw materials, mix them, melt them at 1500°C for 3 hours, and then quench them into glass blocks, grind them by a sand mill, dry them, and sieve them with a 40-mesh screen to obtain BaBSiAl glass-ceramic powder with a D50 particle size of 1.0 to 2.0 μm. The preparation method of the CBAlSi glass-ceramic powder is as follows: weigh calcium carbonate, boric acid, aluminum oxide and silicon powder according to the mass percentage of the raw materials, mix them, melt them at 1500°C for 3 hours, and then quench them into glass blocks, grind them by a sand mill, dry them, and sieve them with a 40-mesh screen to obtain CBAlSi glass-ceramic powder with a D50 particle size of 1.0 to 2.0 μm.
[0075] Table 1. Composition of BaBSiAl glass-ceramic powder
[0076] Glass No. BaO (wt%) <![CDATA[B2O3(wt%)]]> <![CDATA[Al2O3(wt%)]]> <![CDATA[SiO2(wt%)]]> BSi 29 23 10 38
[0077] Table 2. Composition of CBAlSi glass-ceramic powder
[0078] Glass No. CaO (wt%) <![CDATA[B2O3(wt%)]]> <![CDATA[Al2O3(wt%)]]> <![CDATA[SiO2(wt%)]]> CBAlSi-1 25 20 10 45 CBAlSi-2 30 25 15 30
[0079] Examples 1 to 12
[0080] The present embodiments 1 to 12 respectively provide a barium zirconate ceramic-based LTCC raw tape material, which is formed by tape casting of LTCC tape casting slurry; in terms of the mass percentage of the LTCC tape casting slurry, the LTCC tape casting slurry includes 52wt% of inorganic material components and 48wt% of organic material components; the component ratio of the inorganic material in the LTCC tape casting slurry is described in detail in Table 3 below, and the organic material used in embodiments 1 to 12 includes 85wt% of solvent (isopropyl alcohol-butanone mixed solvent), 1wt% of dispersant (castor oil), 11wt% of binder (polyvinyl butyral) and 3wt% of plasticizer (a mixture of dioctyl phthalate and polyethylene glycol) in terms of its mass percentage.
[0081] The formula in Table 3 below is only the formula of the inorganic material used in the LTCC casting slurry used in Examples 1 to 12, that is, the formula of the LTCC casting slurry is not limited to this.
[0082] Table 3. Proportions of Inorganic Materials in Examples 1 to 12
[0083]
[0084]
[0085] The present embodiments 1 to 12 also provide a method for preparing a barium zirconate ceramic-based LTCC raw tape material, wherein the inorganic material, solvent and dispersant are weighed according to the LTCC casting slurry including 52 wt% of inorganic material components and 48 wt% of organic material components, and the ratio of inorganic material and organic material in Table 3, and are put into a ball mill filled with zirconium oxide for ball milling and mixing for 4 hours, and then a binder and a plasticizer are added, and the mixture is ball milled and mixed for another 4 hours to obtain the LTCC casting slurry; after vacuum degassing, the LTCC raw tape material based on barium zirconate ceramic is cast and formed to obtain a smooth appearance, no cracks and good toughness.
[0086] The present embodiments 1 to 12 also provide a LTCC substrate and a preparation method thereof, wherein the preparation method comprises the following steps: first, respectively provide the barium zirconate ceramic-based LTCC raw tape materials in embodiments 1 to 12; then, stack the LTCC raw tape materials for 30 layers to form a blank, and sinter at 880° C. for 3 hours to prepare the corresponding LTCC substrate.
[0087] See also Figure 2 This is a SEM image of the cross-section of the LTCC substrate prepared by sintering the LTCC raw tape material at 880°C for 3 hours in Example 1. It can be seen from the figure that the LTCC substrate formed by sintering the LTCC raw tape material at 880°C for 3 hours in Example 1 has good density. Good density is an important indicator of the LTCC raw tape material. If the internal density is small, that is, there are few internal pores, the formed LTCC substrate has high bending strength, high dielectric constant, and low dielectric loss, which makes the material have a longer service life.
[0088] Performance Testing:
[0089] Dielectric constant and dielectric loss performance test: The barium zirconate ceramic-based LTCC raw tape material prepared in Examples 1 to 12 was cut into the required size of 100mm×100mm, 10 layers were cross-stacked, vacuumed, and isostatically pressed into a green blank, which was then placed in a sintering furnace, first heated to 450°C at a heating rate of 1°C / min at room temperature, and kept at 450°C for 3 hours to remove binder. After the binder removal was completed, the temperature was increased to a certain sintering temperature at a heating rate of 5°C / min, and kept for 3 hours to complete the sintering to form an LTCC substrate; then the SPDR separation column dielectric resonant cavity was used to test the dielectric constant and dielectric loss of the LTCC substrate at 5GHz. Three samples were taken for the formula in each example, and the average value was calculated as the final test data. The test results of the dielectric constant and dielectric loss and the sintering temperature are all shown in Table 4.
[0090] Resonance frequency temperature coefficient test: The LTCC raw tape materials prepared in Examples 1 to 12 are cut into required sizes, 30 layers are cross-laminated, vacuumed, and isostatically pressed into blanks, which are then cut into cylinders with a diameter of 20 mm and a height of 10 mm. The cylindrical blanks are then placed in a sintering furnace, first heated to 450°C at a heating rate of 1°C / min at room temperature, and kept at 450°C for 3 hours to remove binder. After the binder removal is completed, the temperature is increased to a certain sintering temperature at a heating rate of 5°C / min and kept for 3 hours to obtain a cylindrical LTCC substrate. The cylindrical LTCC substrate is then placed in a resonant cavity, and the resonant cavity is then placed in a high and low temperature test chamber to test the resonant frequency temperature coefficient of the cylindrical LTCC substrate between 25 and 85°C. The test results and sintering temperature are shown in Table 4.
[0091] Bending strength test: The LTCC raw tape materials prepared in Examples 1 to 12 were cut into required sizes, 30 layers were cross-laminated, vacuumed, and isostatically pressed into green blanks, which were then cut into strips of 5 mm in height × 5 mm in width × 45 mm in length. The strips were then placed in a sintering furnace, first heated to 450°C at a heating rate of 1°C / min at room temperature, and kept at 450°C for 3 hours to remove binder. After the binder removal was completed, the temperature was raised to a certain sintering temperature at a heating rate of 5°C / min, and kept for 180 minutes to obtain a long strip of LTCC substrates. The bending strength of the long strip of LTCC substrates was then tested using a universal testing machine in accordance with the GB / T 6569-2006 method. The test results and sintering temperature are shown in Table 4.
[0092] Table 4 Test results of dielectric constant, dielectric loss, resonant frequency temperature coefficient and flexural strength of LTCC substrates made of LTCC raw tape materials in Examples 1 to 12 at different sintering temperatures
[0093]
[0094] Application Example 1
[0095] This application example provides a co-fired substrate and a preparation method thereof, wherein the preparation method comprises the following steps:
[0096] A1. Provide the LTCC raw tape material in Example 1, cut it into 4 raw tapes of 100 mm×100 mm in size, print the silver paste pattern of the same shape on each raw tape by screen printing with silver inner electrode paste, and then dry it at 60° C. to obtain a ceramic raw tape printed with silver metal paste; A2. Stack the 4 ceramic raw tapes printed with silver metal paste, press them at 70° C. and 20 MPa pressure to obtain a green body;
[0097] A3. Sinter the green body at 880℃ for 3h to obtain a co-fired substrate of LTCC green tape and silver electrode. Figure 3 This is a SEM image of the cross section of the co-fired substrate prepared in this application example. It can be seen from the image that the LTCC raw tape material formed by tape casting in Example 1 is tightly co-fired with the silver electrode slurry, and there are no bubbles or holes around the silver electrode.
[0098] Comparative Examples 1 to 4
[0099] Comparative Examples 1 to 4 provide a barium zirconate ceramic-based LTCC raw tape material, respectively, wherein the LTCC raw tape material is formed by tape casting of a LTCC tape casting slurry; in terms of the mass percentage of the LTCC tape casting slurry, the LTCC tape casting slurry comprises 52 wt % of an inorganic material component and 48 wt % of an organic material component;
[0100] The composition ratio of inorganic materials in the LTCC casting slurry is described in detail in Table 5 below. The composition ratio of organic materials used is the same as that in Examples 1 to 12, and will not be repeated here.
[0101] Table 5. Ratio of components of inorganic materials in Comparative Examples 1 to 4
[0102]
[0103] Referring to the preparation method and performance test method of the LTCC substrate in the above Examples 1 to 12, various properties of the substrates formed of the LTCC raw tape materials in the present Comparative Examples 1 to 4 were tested. The test results are shown in Table 6 below.
[0104] Table 6 Test results of dielectric constant, dielectric loss, resonant frequency temperature coefficient and flexural strength of substrates made of LTCC raw tape materials in Examples 1 to 4 at different sintering temperatures
[0105]
[0106]
[0107] Application Example 2
[0108] This application example provides a co-fired substrate formed by co-firing the LTCC raw tape material in Comparative Examples 1 to 4 and the silver electrode paste.
[0109] This application example also provides a method for preparing the above-mentioned co-fired substrate, and its preparation method is different from that in Application Example 1 in that it comprises the following steps: in step A1, the LTCC raw tape materials in Comparative Examples 1 to 4 are respectively provided and cut into 4 raw tapes with a size of 100 mm×100 mm; in step A3, the green body is sintered at 900°C for 3 hours; other methods and steps are the same as those in Application Example 1 and will not be repeated here, and finally, co-fired substrates (respectively recorded as co-fired substrate-1, co-fired substrate-2, co-fired substrate-3, and co-fired substrate-4) formed by co-firing the LTCC raw tape materials in Comparative Examples 1 to 4 and the silver electrode paste are prepared. The performance test of the above four co-fired substrates showed that: since there was no low-melting-point microcrystalline glass in the formula of comparative example 1, the sintering shrinkage rate of the LTCC raw tape material was very low after sintering at 900℃ for 3h, and dense sintering could not be completed, and there were many internal pores. However, the silver electrode material was sintered at 900℃ for 3h, and the sintering shrinkage was normal. The two could not achieve synchronous sintering shrinkage when co-fired. Therefore, there were many internal pores in the co-fired substrate-1, the sintering was not dense, and serious warping occurred; and the dielectric constant was low, the dielectric loss was high, the resonant frequency temperature coefficient was +34ppm / ℃, and the bending strength was low. Since there was no low-loss silicate ceramic in comparative example 2, it was not conducive to the full crystallization of microcrystalline glass powder, and the internal crystalline phase of the ceramic after sintering was less, which led to the high dielectric loss of the co-fired substrate-2, but the internal pores of the co-fired substrate-2 were less, the density was good, it was relatively flat, and the co-fired matching was good. Since the amount of low dielectric constant silicate ceramics in comparative example 3 increases, and the temperature coefficient of silicate ceramics is negative, the resonant frequency temperature coefficient of the ceramic substrate after sintering deviates from ±10ppm / ℃, the dielectric constant decreases, the dielectric loss is 0.00078, and the resonant frequency temperature coefficient is -15ppm / ℃; but the internal pores of co-fired substrate-3 are less, the density is OK, it is relatively flat, and the co-fired matching is better. The surface of co-fired substrate-4 is shiny, and there are more internal pores, which is obviously over-burned. This is because with the decrease of the amount of high-melting point BaZrO3 ceramics and the increase of low-melting point ZnZrO3 ceramics, the ceramics will appear surface vitrified and over-burned when sintered at the same sintering temperature, which leads to an increase in over-burned pores inside the ceramic, a decrease in dielectric constant, an increase in dielectric loss, a decrease in bending strength, and a resonant frequency temperature coefficient of -19ppm / ℃; there are more bubbles on the silver surface of co-fired substrate-4, and there are more bubbles around the internal silver electrode.
[0110] In summary, the LTCC raw tape material in the present invention is formed by tape casting of LTCC tape slurry, and the formed LTCC raw tape material has a smooth surface and uniform thickness. The tape-cast LTCC raw tape material is tightly co-fired with the silver electrode slurry, and there are no bubbles or holes around the silver electrode. The Zn in the ZnZrO3 ceramic of the present invention is 2+It can effectively reduce the sintering temperature and ensure that the overall dielectric properties do not decrease; silicate ceramics have low dielectric loss and can be used as small materials to promote the full crystallization of BaZrO3 ceramics and BaBaSiAl microcrystalline glass powder and CBAlSi microcrystalline glass powder during the sintering process, as well as optimize and supplement the deficiencies in the dielectric properties of BaZrO3 ceramics, further reducing the dielectric loss of the composite material. However, the amount of silicate ceramics added should not be too much, as too much will greatly reduce the dielectric constant of the composite material; and the glass resonance frequency temperature coefficient of BaBSiAl microcrystalline glass powder and CBAlSi microcrystalline glass powder is negative, and the dielectric constant is between 6 and 9, so they can be composited with BaZrO3 ceramics. The invention discloses a LTCC raw tape material with a resonant frequency temperature coefficient of nearly zero and a dielectric constant of 10 to 15; the glass transition temperature of the microcrystalline glass powder is 700 to 800°C, and the BaZrO3 ceramic is composited with the low-melting-point microcrystalline glass powder, which can effectively reduce the sintering temperature of the BaZrO3 ceramic and obtain an LTCC material with excellent dielectric properties; in the present invention, by adjusting the mass ratio of each component, the sintering densification temperature of the BaZrO3 ceramic is greatly reduced, ensuring that the prepared barium zirconate ceramic-based LTCC raw tape material can be co-fired with a silver electrode slurry at a low temperature of 880 to 920°C; and the dielectric constant (5GH) of the LTCC substrate formed by stacking the LTCC raw tape is Z ) varies between 10 and 15, dielectric loss (5GH Z ) fluctuates between 0.0007 and 0.0015, the temperature coefficient of the resonant frequency is between ±10ppm / ℃, and the bending strength is above 210MPa. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value. The above embodiments are only illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with this technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.
Claims
1. A barium zirconate ceramic-based LTCC raw tape material, characterized in that: The LTCC raw tape material is formed by tape casting of LTCC tape casting slurry; Calculated by weight percentage of the LTCC casting slurry, the LTCC casting slurry includes 45-55 wt % of an inorganic material component and 45-55 wt % of an organic material component; In terms of the mass percentage of the inorganic material, the inorganic material comprises: 30-70wt% of BaZrO3 ceramics, 5-25wt% of ZnZrO3 ceramics; 1-5wt% of silicate ceramics, and 5-40wt% of microcrystalline glass powder; the silicate ceramics are selected from one or more of CaSiO3 ceramic powder, Zn2SiO4 ceramic powder, Mg2SiO4 ceramic powder, and Li2MgSiO4 ceramic powder; The microcrystalline glass powder is a combination of BaBSiAl microcrystalline glass powder and CBAlSi microcrystalline glass powder; Calculated by mass percentage of the BaBSiAl glass-ceramic powder, the BaBSiAl glass-ceramic powder comprises: 20-40wt% of BaO, 20-40wt% of B2O3, 10-20wt% of Al2O3 and 20-50wt% of SiO2; Calculated by mass percentage of the CBAlSi microcrystalline glass powder, the CBAlSi microcrystalline glass powder comprises: 20-50wt% of CaO, 10-40wt% of B2O3, 10-40wt% of Al2O3 and 25-50wt% of SiO2; The organic material comprises a solvent, a dispersant, a binder and a plasticizer, and the solvent is an alcohol-ketone mixed solvent.
2. The barium zirconate ceramic-based LTCC green tape material according to claim 1, characterized in that: The preparation method of the BaBSiAl microcrystalline glass powder is as follows: barium carbonate, boric acid, aluminum oxide and silicon powder are weighed according to the mass percentage of the raw materials, mixed, melted at 1500-1550° C. for 2-4 hours, then quenched into a glass block, sanded and dried by a sand mill, and sieved with a 40-mesh screen to obtain the BaBSiAl microcrystalline glass powder.
3. The barium zirconate ceramic-based LTCC green tape material according to claim 1, characterized in that: The preparation method of the CBAlSi microcrystalline glass powder is as follows: calcium carbonate, boric acid, aluminum oxide and silicon powder are weighed according to the mass percentage of the raw materials, mixed, melted at 1400-1550° C. for 2-4 hours, then quenched into a glass block, sanded and dried by a sand mill, and sieved with a 40-mesh screen to obtain the CBAlSi microcrystalline glass powder.
4. The barium zirconate ceramic-based LTCC green tape material according to claim 1, characterized in that: The D50 particle size of the BaZrO3 ceramic, the ZnZrO3 ceramic, and the silicate ceramic is 0.7-1.0 μm; And / or, the D50 particle size of the microcrystalline glass powder is 1.0 to 2.0 μm.
5. A method for preparing the barium zirconate ceramic-based LTCC raw tape material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1. Weigh the inorganic material, solvent and dispersant according to the ratio, put them into a ball mill filled with zirconium oxide and mix them by ball milling for 2-4 hours, then add a binder and a plasticizer, and mix them by ball milling for another 2-4 hours to obtain a LTCC casting slurry; S2, the LTCC casting slurry is subjected to vacuum degassing and then cast to obtain a LTCC raw tape material.
6. A LTCC substrate, characterized in that: The LTCC substrate comprises the barium zirconate ceramic-based LTCC green tape material as described in any one of claims 1 to 4.
7. A method for preparing a LTCC substrate, characterized in that: The method for preparing the LTCC substrate comprises the following steps: Providing the barium zirconate ceramic-based LTCC raw tape material as described in any one of claims 1 to 4; The LTCC raw tape material is laminated in multiple layers to form a green blank, which is sintered at 880-920° C. for 150-210 min to prepare a LTCC substrate.
8. The method for preparing a LTCC substrate according to claim 7, wherein: The obtained LTCC substrate has a dielectric constant of 10-15, a dielectric loss of 0.0007-0.0015, and a resonant frequency temperature coefficient of ±10 ppm / ° C. at a test frequency of 5 GHz.
Citation Information
Patent Citations
Microwave dielectric ceramic material with low dielectric constant and preparation method thereof
CN108516825A